2021
DOI: 10.1177/15579883211040920
|View full text |Cite
|
Sign up to set email alerts
|

Biological Responses to Short-Term Maximal Exercise in Male Police Officers

Abstract: The specifics of short-term physical exercise are similar to the immediate reaction demands placed on police officers. Identifying the physiological predisposition to short-term high-intensity exercise in male law enforcement officers will assist in understanding their metabolism and make a significant contribution to a much more personal and individualized workout program. This will improve physical fitness of individual officers, improving their preparedness for such times of emergency. This cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…A bi--phasic etiology arising from monocyte/macrophage sexual dimorphism and leading to the onset of post--nucleotide vaccination myocarditis is further supported by the fact that patients who died of COVID--19 possess cardiac tissue demonstrating a greater number and distribution of CD11+, CD68+ macrophages compared with matched controls or cases of non--COVID--19 myocarditis (137,139). Just as young athletes recovering from COVID--19, demonstrate cardiac MRI abnormalities consistent with myocarditis to a higher degree than is statistically predicted (137,142,143,146). Male elite strength, power and endurance athletes find themselves exposed to an elevated mechanistic risk for the onset of post--SARS--CoV--2 nucleotide vaccination myocarditis secondary to: 1) the potential for exceedingly high peak plasma concentrations of vaccine--induced, self--generated SARS--CoV--2 spike protein/S1 issuing forth from the highly proficient protein synthetic apparatus possessed elite athlete skeletal muscle tissue, 2) the expanded capillary network possessed by elite athletes, 3) the robust innate immune function of elite athletes caused in part by the higher testosterone levels possessed by elite athletes, relative to age--matched controls and lesser performing athletes (146).…”
Section: Sexual Dimorphism Of Monocyte/macrophage Inflammatory Secretomesmentioning
confidence: 92%
See 1 more Smart Citation
“…A bi--phasic etiology arising from monocyte/macrophage sexual dimorphism and leading to the onset of post--nucleotide vaccination myocarditis is further supported by the fact that patients who died of COVID--19 possess cardiac tissue demonstrating a greater number and distribution of CD11+, CD68+ macrophages compared with matched controls or cases of non--COVID--19 myocarditis (137,139). Just as young athletes recovering from COVID--19, demonstrate cardiac MRI abnormalities consistent with myocarditis to a higher degree than is statistically predicted (137,142,143,146). Male elite strength, power and endurance athletes find themselves exposed to an elevated mechanistic risk for the onset of post--SARS--CoV--2 nucleotide vaccination myocarditis secondary to: 1) the potential for exceedingly high peak plasma concentrations of vaccine--induced, self--generated SARS--CoV--2 spike protein/S1 issuing forth from the highly proficient protein synthetic apparatus possessed elite athlete skeletal muscle tissue, 2) the expanded capillary network possessed by elite athletes, 3) the robust innate immune function of elite athletes caused in part by the higher testosterone levels possessed by elite athletes, relative to age--matched controls and lesser performing athletes (146).…”
Section: Sexual Dimorphism Of Monocyte/macrophage Inflammatory Secretomesmentioning
confidence: 92%
“…Male elite strength, power and endurance athletes find themselves exposed to an elevated mechanistic risk for the onset of post--SARS--CoV--2 nucleotide vaccination myocarditis secondary to: 1) the potential for exceedingly high peak plasma concentrations of vaccine--induced, self--generated SARS--CoV--2 spike protein/S1 issuing forth from the highly proficient protein synthetic apparatus possessed elite athlete skeletal muscle tissue, 2) the expanded capillary network possessed by elite athletes, 3) the robust innate immune function of elite athletes caused in part by the higher testosterone levels possessed by elite athletes, relative to age--matched controls and lesser performing athletes (146). In addition to androgen stimulation, the innate immune function of elite athletes is enhanced as a result of regular, intense physical training, with monocyte/macrophage function being especially enhanced (142,143). The enhanced mechanistic risk incurred by elite male athletes also extends to their female elite athlete counterparts.…”
Section: Sexual Dimorphism Of Monocyte/macrophage Inflammatory Secretomesmentioning
confidence: 99%
“…It is well known that glands activity and hormones production (i.e., cortisol and thyroid hormones) are affected by physical activity ( Deligiannis et al, 1993 ; Dergaa, Ben Saad, et al, 2021 ; Souissi et al, 2021 ). The thyroid is one of the most affected glands by the submaximal exercise ( Deligiannis et al, 1993 ; Gagnon et al, 2014 ; Hackney & Saeidi, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…To resume, because physical exercise increases the activity of thyroid glands ( Deligiannis et al, 1993 ; Dergaa, Ben Saad, et al, 2021 ; Souissi et al, 2021 ) and rises the blood level of melatonin ( Escames et al, 2012 ), the increase of melatonin during exercise may be linked to a rise in TSH. However, to the best of the authors’ knowledge, no previous study has investigated the acute combined effects of daytime melatonin ingestion and exercise on humans’ thyroid hormones’ responses.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin secretion follows a diurnal cycle, with the lowest temperature levels occurring in the early morning following the highest melatonin level and the highest temperature levels occurring in the late evening following the lowest melatonin level (1,2). Melatonin levels may peak 30 times greater than normal during the daytime early in the morning, when the body temperature is at its lowest (3)(4)(5)(6). Additionally, it was recently found that melatonin release may be lunar-dependent, with a peak recorded around the full moon versus the new moon (7,8).…”
Section: Introductionmentioning
confidence: 99%